Platelet glycoprotein VI genetic quantitative and qualitative defects - Martine Jandrot-Perrus; Cedric Hermans; Diego Mezzano (Platelets, 2019)
Platelet membrane glycoprotein VI (GPVI) is increasingly recognized as an important receptor for thrombus formation and growth. Numerous arguments have been published indicating that GPVI plays a major role in thrombosis without being essential for physiological hemostasis. In humans, GPVI deficiencies are rarely reported. These are most often deficiencies occurring in the context of autoimmunity and, more rarely, genetic deficits. The purpose of this review is to compile data on the quantitative and qualitative genetic abnormalities of GPVI.